Selection responses for some agronomic traits in hexaploid triticale - Manero de Zumelzu, D.=700 1 Costero, B.; Cavaleri, P.; Maich, R.
(En)
ilus., 11 ref.
Keywords: TRITICOSECALE; SELECCION; NUMERO DE GRANOS; INDICE MEIOTICO; RESPUESTAS DIRECTAS Y CORRELACIONADAS